The Social Meaning behind Hadith Reception of Nisfu Sya’ban Night Prayer at PP. Putera Menara Al-Fattah Tulungagung - Ubaidillah Hasan; Sherina Wijayanti (Islamika Inside: Jurnal Keislaman dan Humaniora, 2023)
Abstract: This article presents a religious phenomenon that fused with the cultural rituals of the society which can influence the dialectic of behavior in life. This paper aims to explore the societies’ understanding of the hadith reception in the tradition of nisfu sya'ban night prayers. This study focuses on how the implementation of nisfu sya'ban night prayer’s tradition in the historical and normative scope, society reception and its psychological impact on the congregants. The research method of this study was qualitative with a living hadith approach using the theory of Petter L. Berger and Karl Mannheim through interviews, observation, documentation, and literature study as a research instrument. The results of this study were: First, the tradition of nifsu sya'ban night prayer appeared from the awareness of a hadith which was strengthened in the book of Ihya. This hadith was used as the basis for carrying out the Nisfu Sha'ban night prayer with a total of one hundred rakhas. Second, the tradition of nisfu sya'ban night prayer was carried out because of obedience to the Kyai. Third, the night of nisfu sya'ban’s tradition can influence the motivation of spirituality and healthy aspects. The night tradition of nifsu sya'ban is the variety of living hadith traditions in Indonesia.